Treatment of palm oil mill effluent via chitosan based on flocculation : a study of different concentration of solid and liquid chitosan - Siti Hajar, Mustapa (2008)
Chitosan is a natural cationic biopolymer was used as a coagulant in treatment of residual oil and suspended solids in palm oil mill effluent (POME). POME is one of the major oily wastewater in Malaysia. Like other industries, palm oil processing industries also generate large quantities of effluent, when discharged untreated into watercourses, adversely affects aquatic life and domestic water supply. The objective of this study is to treat the palm oil mill effluent (POME) using the natural polymer, Chitosan based on flocculation. POME was treated using solid and liquid Chitosan to study the effect on oil removal, turbidity and biochemical oxygen demand (BOD). A study of flocculation was carried out using a jar-test apparatus. The results obtained showed that at 6.0% of liquid dosage used for treatment has reduced 80% of residual oil and 97% of turbidity. In term of Biochemical Oxygen Demand, the results showed increasing in BOD reading. The results obtained proved that Chitosan in liquid form was comparatively more efficient to solid Chitosan in removing residual oil and turbidity.